INFLUENCE OF THE INVESTMENTS IN INNOVATION SPHERE ON PROFIT OF THE MACHINE-BUILDING ENTERPRISES OF THE ROSTOV AREA - K.A. BARMUTA (Advanced Engineering Research)
In conditions of an aggravation of competitive struggle with the foreign companies the production of a question about determining influence of innovation development of the domestic enterprises on final results of their activity becomes especially urgent. The character of influence of the investments in innovation sphere on volume of production is revealed, of works and services and balance profit of the machine-building enterprises and the conditions of maximum effect from innovation activity of one of the basic industries of the Rostov area are determined.